Pericoronitis of lower third molars teeth: Female: a case report - AHMED, YASER; ALAQILI, SAMAR (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
An inflammation of the soft tissue surrounding of the partial eruption impacted mandibular third molars. The clinical appearance are edema, redness, pain in the left lower thirds and bad oral hygiene with halitosis. It's a regular round in shape, its well-defined margins, measuring 2.5mm It was covered with thin mucosal tissue. The Pericoronitis occurrence in the female more than male in Yemen.Case situation: Partial impacted teeth and inflammation of the surrounding soft tissue in the mouth of a 23 years. Yemeni females: In the left posterior Mandibular third molar (Wisdoms)Conclusion: The Pericoronitis occurrence in the female more than male in Yemen because the jaw of the female is a smaller therefore haven't space for eruption of the third molar.